2023
DOI: 10.3389/fpls.2022.1009244
|View full text |Cite
|
Sign up to set email alerts
|

Marker-trait association analyses revealed major novel QTLs for grain yield and related traits in durum wheat

Abstract: The growing global demand for wheat for food is rising due to the influence of population growth and climate change. The dissection of complex traits by employing a genome-wide association study (GWAS) allows the identification of DNA markers associated with complex traits to improve the productivity of crops. We used GWAS with 10,045 single nucleotide polymorphism (SNP) markers to search for genomic regions associated with grain yield and related traits based on diverse panels of Ethiopian durum wheat. In Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 119 publications
1
12
0
Order By: Relevance
“…The observed moderate to high values of broad-sense heritability and the consistency of trait records evidenced by the significant correlations between the crop seasons suggest that a considerable part of the variation is due to inherent genetic differences among the accessions. These results agree with similar findings in bread and durum wheat for GPC [ 19 , 25 , 27 , 40 ], and TKW [ 13 , 41 ]. Given that the panel contains historical and contemporary varieties released or collected between 1925 and 2010, it is possible that the recorded genetic variance—especially for TKW—is inflated.…”
Section: Discussionsupporting
confidence: 92%
“…The observed moderate to high values of broad-sense heritability and the consistency of trait records evidenced by the significant correlations between the crop seasons suggest that a considerable part of the variation is due to inherent genetic differences among the accessions. These results agree with similar findings in bread and durum wheat for GPC [ 19 , 25 , 27 , 40 ], and TKW [ 13 , 41 ]. Given that the panel contains historical and contemporary varieties released or collected between 1925 and 2010, it is possible that the recorded genetic variance—especially for TKW—is inflated.…”
Section: Discussionsupporting
confidence: 92%
“…A study by [ 85 ] also revealed multiple MTAs on chromosome 18 for cassava starch pasting properties, indicating the high LD of markers on this chromosome. Multiple MTAs have also been detected for flowering traits in Indian mustard ( Brassica juncea ) [ 57 ] and grain yield and related traits in durum wheat ( Triticum turgidum ) [ 90 ]. Other traits had only one MTA on a chromosome, such as S15_11747301 on chromosome 15 (associated with branching, branch type, branching levels, and number of nodes).…”
Section: Discussionmentioning
confidence: 99%
“…To meet the future demand for durum wheat grains despite the climatic changes ( Mulugeta et al., 2023 ), a significant increase in production is necessary ( Sakuma and Schnurbusch, 2020 ). The indirect selection of production-related traits under more stringent genetic control is a potential solution to favor rapid pyramiding of useful alleles ( Tadesse et al., 2019 ; Colasuonno et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NAM population was genotyped using the 25K TraitGenetics array (GmbH, Gatersleben, Germany), which combines the most polymorphic markers from the Axiom Breeder Array and the Illumina Infinium 90K ( Mulugeta et al., 2023 ). High-fidelity polymorphic SNPs were defined as those having less than 1% missing data and a minor allele frequency superior to 10% as can be expected in a biparental population.…”
Section: Methodsmentioning
confidence: 99%